The Effect of Think Pair Share (TPS) Learning Model With Problem Solving Approach on the Student's Math Communication in MA DA Jarowaru " - Samsuriadi Samsuriadi; Muhammad Ali Imron (Malikussaleh Journal of Mathematics Learning (MJML), 2019)
The purpose of this study was to determine the effect of Think Pair Share (TPS) learning models with problem solving approaches. The approach used in this research is a qualitative approach with the type of experimental research "The effect of Think Pair Share (TPS) learning model with problem solving approach to students' mathematical communication in MA DA Jerowaru. Model Pair Pair Share (TPS), as the name "Thinking" learning begins with the teacher asking questions or issues related to the lesson for students to think about, "pairing", at this stage the teacher asks students to pair up pairs. Give the couple a chance to discuss. It is hoped that this discussion will be able to deepen the meaning of the answers they have thought through intersubjectives with their partners. The results of intersubjective discussions in each pair of results are discussed with the whole class pair. This stage is known as "sharing" in this activity. It is expected that question and answer will occur which encourages the integrative management of knowledge. Added to this is the emphasis on problem solving, namely the Problem Solving approach. Problem Solving is an approach that teaches students how to solve a problem. Meanwhile, according to Heriawan (in Istiqoma and Rusdi, 2012: 92). Problem Solving is a way of presenting learning material by making problems as a starting point for discussion to be analyzed in an effort to find solutions or answers by students.